2020
DOI: 10.1111/jfd.13242
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequence modification in the highly polymorphic region (HPR) of the hemagglutinin gene of the infectious salmon anaemia virus (ISAV) suggests intra‐segmental template switching recombination

Abstract: The ISAV has a genome composed of eight segments of (–)ssRNA, segment 6 codes for the hemagglutinin–esterase protein, and has the most variable region of the genome, the highly polymorphic region (HPR), which is unique among orthomyxoviruses. The HPR has been associated with virulence, infectivity and pathogenicity. The full length of the HPR is called HPR0 and the strain with this HPR is avirulent, in contrast to strains with deleted HPR that are virulent to varying degrees. The molecular mechanism that gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…HPRΔ variants (deleted) can cause disease whereas HPR0 variants (no deletion) are not known to cause disease (Cook‐Versloot et al., 2004 ; Cunningham et al., 2002 ). With the exception of an artificial recombinant HPR0 variant (Cardenas et al., 2020 ), only HPRΔ variants are known to grow in cell culture (Aamelfot et al., 2016 ; OIE, 2021 ) and evidence suggests that HPRΔ originate from HPR0 variants, suggesting that transient variants with some but not all virulence markers may exist (Christiansen et al., 2017 ; Gagne & LeBlanc, 2018 ). On S5, a prerequisite of virulence seems to be a Q 266 →L 266 substitution or Q 266 with an insertion close to the putative cleavage site (Devold, 2006 ; Markussen et al., 2008 ).…”
mentioning
confidence: 99%
“…HPRΔ variants (deleted) can cause disease whereas HPR0 variants (no deletion) are not known to cause disease (Cook‐Versloot et al., 2004 ; Cunningham et al., 2002 ). With the exception of an artificial recombinant HPR0 variant (Cardenas et al., 2020 ), only HPRΔ variants are known to grow in cell culture (Aamelfot et al., 2016 ; OIE, 2021 ) and evidence suggests that HPRΔ originate from HPR0 variants, suggesting that transient variants with some but not all virulence markers may exist (Christiansen et al., 2017 ; Gagne & LeBlanc, 2018 ). On S5, a prerequisite of virulence seems to be a Q 266 →L 266 substitution or Q 266 with an insertion close to the putative cleavage site (Devold, 2006 ; Markussen et al., 2008 ).…”
mentioning
confidence: 99%
“…However, in univariable analysis, TTD was much shorter for cases due to the ISAV-HPR0 variant, suggesting that fish are exposed much earlier during the production cycle with this virus variant, which likely supports the hypothesis that this is a circulating variant in the environment and could be the precursors of HPRΔ variants. The variant ISAV-HPR0 is considered a risk factor for developing clinical ISAV outbreaks as there is evidence for the conversion of ISAV-HPR0 into ISAV-HPRΔ in other regions (Cárdenas et al 2020). Our limited data did not provide any evidence to support this hypothesis.…”
Section: Parametersmentioning
confidence: 63%
“…The variant ISAV‐HPR0 is considered a risk factor for developing clinical ISAV outbreaks as there is evidence for the conversion of ISAV‐HPR0 into ISAV‐HPRΔ in other regions (Cárdenas et al. 2020). Our limited data did not provide any evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Before the characterization of the infective phenotype, the synthetic reassortant viruses were genetically characterized to confirm the rearrangement and segments 5 and 6 genotype, since it has been shown that ISAV can modify its HPR region in vivo [ 16 ]. We have also described this phenomenon with our reverse genetics system in vitro [ 30 ]. However, we have demonstrated that it is possible to obtain genetically stable viruses via at least three passages with this system.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the supernatant was discarded, the cells were washed three times with PBS, and 1 mL of culture media with 10% FBS was added. The plates were maintained for seven days at 15 °C, and the process was repeated until obtaining three blind passages [ 30 ].…”
Section: Methodsmentioning
confidence: 99%